Implementation of employee assistance programme under NRF: a case study - Dubey, Rameshwar (1998)
In this paper the experiences of National Productivity Council as an Employee Assistance Centre (EAC) at Bangalore, Oorgaum and Mysore in the state of Karnataka under National Renewal Fund (NRF) has been described. The paper details and the number of employees rationalised from different organisations their status and the courses identified and institutional infrastructure available for retraining of the employees. The paper also describes the methodology adopted in survey and problems encountered in locating rationalised employees, counselling them with possible solutions and observations regarding scope of future gainful employment. - Reproduced
Keywords: Management; National renewal fund (NRF); Employee assistance programmes; Case studies; Personnel management